Atrazine Removal in Municipal Secondary Effluents by Fenton and Photo‐Fenton Treatments. Issue 12 (15th October 2013) - De Luca, A.; Dantas, R. F.; Simões, A. S. M.; Toscano, I. A. S.; Lofrano, G.; Cruz, A.; Esplugas, S.
Abstract Alternative water sources, including effluents from municipal wastewater treatment plants (MWTP) are necessary to meet increasing water demand. Advanced oxidation processes based on the Fenton reaction were applied to remove atrazine from the secondary effluents of a MWTP that uses activated sludge. Fenton, UV‐A photo‐Fenton, and UV‐C photo‐Fenton treatments were tested. Atrazine removal percentages were around 20 % for Fenton, 60 % for UV‐A photo‐Fenton and 70 % for UV‐C photo‐Fenton treatments, respectively. Organic matter mineralization by Fenton treatment was monitored and no significant reduction was observed. However, organic matter oxidation in terms of COD reduction of around 30 and 40 % were achieved by Fenton and photo‐Fenton processes, respectively. The photo‐Fenton process with UV‐C is a useful technique for atrazine degradation, leading to higher degradation than with UV‐A while also being more attractive in an economic point of view.